Evaluasi Kurikulum dalam Mata Pelajaran Pendidikan Agama Islam - Amalia, Ulfah Nisa Nurul; Wildan, Syakur (ALSYS, 2023)
Evaluation is a process in an effort to collect information that can be used as consideration for making decisions. Curriculum is an overall activity designed by schools to provide various experiences to students, both inside and outside the classroom. While the assessment process consists of three components, namely gathering information, making judgments, and making decisions. To find out how well Islamic education implemented by schools can be seen from the running of the school's PAI curriculum itself. The purpose of this study was to determine the implementation of the Islamic Religious Education (PAI) curriculum and the assessment of student learning outcomes in PAI subjects. This research is more focused on library research, which is a study that focuses on collecting library data. Researchers conducted a study on the evaluation of the Islamic religious education curriculum. The results of curriculum evaluation can also be used by teachers, school principals and other education implementers, in understanding and assisting student development, selecting lesson materials, selecting teaching aids and methods, assessment methods and other educational facilities.